2021
DOI: 10.1021/acssuschemeng.1c01468
|View full text |Cite
|
Sign up to set email alerts
|

Fast and Stable Electrochemical Production of H2O2 by Electrode Architecture Engineering

Abstract: Fast and stable production of hydrogen peroxide (H 2 O 2 ) through electrochemical pathways is crucial for wastewater treatment applications. With this objective, herein, we report an integrated and superaerophilic electrode composed of atomically dispersed Ni−O−C site-enriched carbon nanosheets (IS-NiOC electrode) for electrochemical oxygen reduction to produce H 2 O 2 . Both experimental and theoretical results have proven that atomically dispersed Ni−O−C sites enable a low overpotential (260 mV at 0.1 mA cm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 60 publications
0
24
0
Order By: Relevance
“…Furthermore, the prominent stability (Figure S10) and outstanding performance in a practical electrolysis system (Figures S11–S13) demonstrated the great potential for industrial applications. It is worth noting that, compared with previously reported catalysts in a neutral system, , the M-Zn NP -O-C catalyst still ranked among the best in terms of both catalytic merits (Table S1) and Tafel−θ analysis (Figures e and S14).…”
mentioning
confidence: 65%
See 2 more Smart Citations
“…Furthermore, the prominent stability (Figure S10) and outstanding performance in a practical electrolysis system (Figures S11–S13) demonstrated the great potential for industrial applications. It is worth noting that, compared with previously reported catalysts in a neutral system, , the M-Zn NP -O-C catalyst still ranked among the best in terms of both catalytic merits (Table S1) and Tafel−θ analysis (Figures e and S14).…”
mentioning
confidence: 65%
“…According to the previous studies, , we hypothesized that the carbon sites adjacent to the metallic Zn nanoparticle and bridging oxygen would have an optimized electronic structure and be active sites for the 2e – ORR. To prove this assumption, we first utilized thiocyanide (SCN – ) to poison metal Zn sites (Figure S21), and the results demonstrated that the activity of M-Zn NP -O-C was almost unchanged after the addition of SCN – ; the active sites for the 2e – ORR are the carbon sites rather than the metal sites.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…X-ray photoelectron spectroscopy (XPS) full spectra confirm the existence of Ni 2p, Ru 3p, O 1s, C 1s, and Ru 3d for O-RuNi@C-T (Figure S9 in the Supporting Information). Two peaks (see Figure b, as well as Figure S10 in the Supporting Information) at ∼856.01 and 853.24 eV belong to the 2p 3/2 peaks of Ni 2+ and Ni 0 , respectively. Compared with Ni@C-400 (Figure S11 in the Supporting Information), the Ni 0 peak for O-RuNi@C-400 negatively shifts ∼0.11 eV (Figure S12 in the Supporting Information), demonstrating the existence of the electron transfer from Ni to Ru. Besides, with the increase of carbonization temperature, the Ni 0 peak negatively shifts, and the peak intensity of Ni 2+ weakens, which is due to the fact that the ratio of Ni–O bond decreases.…”
Section: Resultsmentioning
confidence: 98%
“…2 eV correspond to C−O−C, C�O, and Ni−O−C, respectively 30,38. As shown in O 1s spectrum of Ni@C-400, we can see the Ni−O−C peak, but compared to O-RuNi@C-400, the Ni−O−C peak is relatively weak.…”
mentioning
confidence: 83%